2014
DOI: 10.1155/2014/421954
|View full text |Cite
|
Sign up to set email alerts
|

Designer Self-Assembling Peptide Nanofiber Scaffolds Containing Link Protein N-Terminal Peptide Induce Chondrogenesis of Rabbit Bone Marrow Stem Cells

Abstract: Designer self-assembling peptide nanofiber hydrogel scaffolds have been considered as promising biomaterials for tissue engineering because of their excellent biocompatibility and biofunctionality. Our previous studies have shown that a novel designer functionalized self-assembling peptide nanofiber hydrogel scaffold (RLN/RADA16, LN-NS) containing N-terminal peptide sequence of link protein (link N) can promote nucleus pulposus cells (NPCs) adhesion and three-dimensional (3D) migration and stimulate biosynthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 34 publications
4
18
0
Order By: Relevance
“…Therefore, constructing a tissue engineering matrix material with a suitable structure and biological activity, and providing an appropriate stromal environment for IVD stem/progenitor cells are two important methods of effective treatments for IVD degeneration 96e100 . Polypeptide self-assembled nanofiber gels are one of the latest materials in tissue engineering 42,99,101 . They have been used for three-dimensional culture of cells, repair of defective tissue, and drug/cytokine release.…”
Section: Constructing a Tissue Engineering Matrix Materials With A Suimentioning
confidence: 99%
“…Therefore, constructing a tissue engineering matrix material with a suitable structure and biological activity, and providing an appropriate stromal environment for IVD stem/progenitor cells are two important methods of effective treatments for IVD degeneration 96e100 . Polypeptide self-assembled nanofiber gels are one of the latest materials in tissue engineering 42,99,101 . They have been used for three-dimensional culture of cells, repair of defective tissue, and drug/cytokine release.…”
Section: Constructing a Tissue Engineering Matrix Materials With A Suimentioning
confidence: 99%
“…We and others have previously demonstrated that Link N can act as an anabolic agent in the disc enhancing proteoglycan synthesis and depleting proteinase expression. [34][35][36][37][38]44,45,48,[52][53][54][55][56][57][58][59][60] We have shown that Link N can maintain its anabolic effects in an inflammatory milieu when human IVD cells were exposed to IL-1. 36 Using a rabbit model of IVD degeneration, we have generated data indicative of the role of Link N and Short Link N, a recently discovered fragment of the Link N peptide, in disc repair.…”
Section: Discussionmentioning
confidence: 99%
“…In Table 1, we show that Link N is an ideal IVD target profile based on the present study and other published work. [35][36][37]45,[52][53][54][55][56][57][58][59][60] In Table 2, a summary of the clinical and market opportunities for Link N is presented.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25] They are capable of self-replication and differentiation into osteocytes in appropriate culture conditions and can contribute to the regeneration of mesenchymal tissues such as bone. [3,26] BM-MSCs can be rapidly expanded ex vivo without loss of their multi-lineage differentiation potential. [13] They are readily available and amenable to genetic manipulation.…”
Section: Discussionmentioning
confidence: 99%